PLASMA TOTAL HOMOCYSTEINE, LIPOPROTEIN (A) AND VON WILLEBRAND FACTOR LEVELS IN ASSESSMENT OF METABOLIC CONTROLS OF CHILDREN WITH TYPE I DIABETES MELLITUS - Ertugrul, Sabahattin; Sen, Yasar; Yilmaz, Erdal; Aydin, Mustafa; Ustundag, Bilal (Nobel Ilac, 2014)
Objective: Diabetes is a significant risk factor for early onset of atherosclerosis. In this study, it was aimed to determine whether total homocysteine (tHcy), lipoprotein(a) [Lp(a)] and von Willebrand factor (vWF) levels have an early predictive value like glycolysated hemoglobin (HbA1c) levels in assessment of metabolic condition of children with type I diabetes. Material and Method: Study group consisted of 65 children and adolescents who had type I diabetes but not clinical findings of microvascular and macrovascular complications and 20 healthy children and adolecents with the same age group and gender Blood samples were obtained from diabetic patients, treatments were arranged and patients were followed up (Group I diabetic patients). Patients were re-evaluated at the end of 1 year and blood samples were obtained again (Group H diabetic patients). Results: A statistically significant difference was found between the first (11.1 +/- 3.3 mu mol/L) and the second tHcy levels (10.2 +/- 1.7 mu mol/L) of diabetic patients and tHcy levels of control group (8.9 +/- 2 mu mol/L)(p<0.05 and <0.01, respectively). A statistically significant difference was found between the first (10.4 +/- 5.4 mg/dl) and the second Lp(a) levels (9.0 +/- 4.3 mg/dl) of diabetic patients and Lp(a) levels of control group (5.3 +/- 2.8 mg/dl)(p<0.01 and <0.001, respectively). A statistically significant difference was not found when vWF levels of diabetic groups I and II and control group were compared (p>0.05). A statistically significant positive correlation was found between tHcy and HbA1c, microalbumin in Group I diabetic patients (r=0,389, p=0,02; r=0,286, p=0,034, respectively). A statistically significant positive correlation was found between HbA1c and homocysteine, vWF, microalbumin (r=0,428, p=0,001; r=0,328, p=0,024; r=0,742, p=0,001, respectively) and vWF and microalbumin levels (r=0,560, p=0,001) in Group II diabetic patients. Conclusion: In conclusion, that tHcy and Lp(a) could be beneficial for assessment of metabolic control of diabetes, treatments toward reducing the complications of diabetes or the outcomes of additions to diet.
Keywords: Diabetes mellitus; homocysteine; lipoprotein (a); von Willebrand factor